Postpartum fevers, a rare presentation of secondary hemophagocytic lymphohistiocytosis. Issue 3 (17th March 2023) - Lee, Jacqueline; Pham, Brian; Karanjawala, Zarir E.; Adesina, Oyebimpe
Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a rare disease of excessive immune system activation. We report a case of HLH in a 20‐year‐old primigravid woman who presented with postpartum fevers. She was successfully treated with dexamethasone and anakinra, a deviation from the HLH‐94 protocol, to preserve her ability to breastfeed. Abstract : HLH is an important differential diagnosis for postpartum fevers, cytopenias, and elevated liver enzymes. To treat postpartum HLH, anakinra and dexamethasone may be a reasonable alternative to the HLH‐94 protocol in patients who wish to breastfeed